Phosphorus-containing nanoparticles: biomedical patents review. (May 2015) - Shcharbin, Dzmitry; Shcharbina, Natallia; Shakhbazau, Antos; Mignani, Serge; Majoral, Jean-Pierre; Bryszewska, Maria
<x xml:space="preserve">Abstract</x> Introduction: The beginning of the nano-era started with the appearance of artificial nanosized supramolecular systems called nanomaterials and nanoparticles (NPs). Areas covered: In the present review, we have analyzed the patents on phosphorus-based nanomaterials (fullerenes, quantum dots [QDs], graphene, liposomes, dendrimers, gold and silver NPs) in biology and medicine. Their impact in treatment of cancer, viral infections and cardiovascular diseases is discussed. Expert opinion: Liposomes and dendrimers had the highest number of biomedical patents. The third candidates were QDs and the fourth and fifth were gold and silver NPs. Fullerenes and carbon nanotubes have the fewest applications in biology and medicine. Thus, our first conclusion was about the 'unifying nanotoxicology paradigm', that 'soft' NPs are significantly more biocompatible than 'hard' NPs. There has been a trend of these nanomaterials being applied in medicine drug and gene delivery, visualization of cells and pathologic processes, using them as antivirals and antimicrobials, contrast agents, antioxidants and photosensitizers. It was unexpected that no patents were found in which phosphorus NPs were used in 3D printing of bones and other biological tissues. The conclusion reached is that nanomaterials are promising tools in future medical applications.